Relationships of attention and arousal are responsible for action in sports - Mikicin Mirosław (Biomedical Human Kinetics, 2022)
Study aim: The most important psychological mechanisms that are responsible for sports activity are arousal and attention. Study aim the relationships between the level of arousal and the level of attention, an attempt has been made to explain the mechanisms responsible for sportsman activity.